Sistem Kendali dan Monitoring Pada Alat Tetas Telur Berbasis Mikrokontroler - Irma Saraswati; Rian Fahrizal; Heri Haryanto; Dhitya Pujarama (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2023)
Internet of Things (IoT) is a scientific development that is very promising to optimize and simplify life through the internet network. This research tries to utilize IoT technology in the field of animal husbandry, which is monitoring and control in the process of duck egg raising. The parameters that are controlled and monitored are temperature and humidity. The built- in IoT system allows users to remotely monitor temperature and humidity conditions on the hatching device. This egg incubator uses 2 lamps that function as heaters with 10 watts of power, 2 pumps as humidity control and is equipped with a motor that functions to rotate the egg rack. This tool works automatically by comparing the temperature and humidity of the DHT22 sensor with a setpoint on the microcontroller. Then the temperature and humidity values are displayed on the LCD and on the Android Application that has been made. The response of the temperature control is, the delay time (Td) is 140 seconds, the rise time (Tr) is 220 seconds, the peak time (Tp) is 240 seconds, and the maximum overshoot (Mp) is 4.21% (1.60 ° C)